2018
DOI: 10.1063/1.5050235
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of surface hopping approaches for capturing metal-molecule electron transfer: A broadened classical master equation versus independent electron surface hopping

Abstract: The symmetrical quasi-classical approach to electronically nonadiabatic dynamics applied to ultrafast exciton migration processes in semiconducting polymers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 73 publications
0
40
0
Order By: Relevance
“…relies on an independent electrons and cannot directly include electron-electron repulsion (as would be found in a realistic ab initio Hamiltonian); finite temperature effects are also difficult [66].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…relies on an independent electrons and cannot directly include electron-electron repulsion (as would be found in a realistic ab initio Hamiltonian); finite temperature effects are also difficult [66].…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, Shenvi et al [64] originally developed the independent electron surface hopping model. Nevertheless, for all of its successes [65], the IESH model relies on an independent electrons and cannot directly include electron-electron repulsion (as would be found in a realistic ab initio Hamiltonian); finite temperature effects are also difficult [66].…”
Section: Discussionmentioning
confidence: 99%
“…To make the computational cost affordable while still treating many electronic states, the Hamiltonian models independent electrons such that the electronic wave function is always the simple product of one-electron orbitals. In practice, the IESH algorithm is a powerful approach for simulating dynamics at surfaces, , and we have recently demonstrated that IESH does agree with Marcus theory under the right conditions . The only hiccup with IESH is that, for gas-phase scattering calculations (i.e., without a nuclear bath), there is no natural means to include electronic relaxation of the Fermi sea bath to the Fermi level without introducing artifacts; this remains an outstanding question for future development.…”
Section: Introductionmentioning
confidence: 99%
“…A second approach to this same problem is the broadened classical master equation (BCME), 27,89 which was recently developed by our research group and compared with IESH. 90 BCME extrapolates the CME to the strong molecular-metal coupling regime (Γ > kT ). The BCME yields accurate and efficient results for the Anderson-Holstein model 90,91 and has been recently applied to electrochemical model problems.…”
Section: Existing Semi-classical Approaches To Nonadiabatic Dynamics ...mentioning
confidence: 99%
“…90 BCME extrapolates the CME to the strong molecular-metal coupling regime (Γ > kT ). The BCME yields accurate and efficient results for the Anderson-Holstein model 90,91 and has been recently applied to electrochemical model problems. 92 However, at bottom, the BCME method is formulated in a (modified) molecular diabatic picture, which has both upsides and downsides.…”
Section: Existing Semi-classical Approaches To Nonadiabatic Dynamics ...mentioning
confidence: 99%